Diversity and Regulation of S-Adenosylmethionine Dependent Methyltransferases in the Anhydrobiotic Midge - Deviatiiarov, Ruslan (Insects, 2020)
SIMPLE SUMMARY: Adaptation to anhydrobiotic conditions of Polypedilum vanderplanki at the larval stage is accompanied by specific genome features and related regulatory mechanisms. The unusual diversity of paralogous genes located in gene clusters with a strong dehydration specific response is thought to underlie the desiccation tolerance of the insect. One of the most representative clusters consists of the gene coding protein, L-isoaspartate O-methyltransferases (PIMT), but it remains poorly characterized. In our work, by applying the transcriptomic RNA-seq approach on desiccated-rehydrated larvae, we showed that these genes have significant dissimilarities in their transcriptional activity within the group, but also in comparison with the expression profiles of other defined types of S-adenosylmethionine dependent methyltransferases active in the larvae. We also showed the standard methylation activity of two PIMTs, while the rest of the 12 tested proteins lacked an enzymatic function in normal physiological conditions. These results, together with in silico modelling, determine the heterogeneity of the group in terms of its role in the adaptation to anhydrobiosis. ABSTRACT: Multiple co-localized paralogs of genes in Polypedilum vanderplanki’s genome have strong transcriptional response to dehydration and considered to be a part of adaptation machinery at the larvae stage. One group of such genes represented by L-isoaspartate O-methyltransferases (PIMT). In order to highlight specific role of PIMT paralogization in desiccation tolerance of the larvae we annotated and compared S-adenosylmethionine (SAM) dependent methyltransferases of four insect species. From another side we applied co-expression analysis in desiccation/rehydration time course and showed that PIMT coding genes could be separated into five clusters by expression profile. We found that among Polypedilum vanderplanki’s PIMTs only PIMT1 and PIMT2 have enzymatic activity in normal physiological conditions. From in silico analysis of the protein structures we found two highly variable regions outside of the active center, but also amino acid substitutions which may affect SAM stabilization. Overall, in this study we demonstrated features of Polypedilum vanderplanki’s PIMT coding paralogs related to different roles in desiccation tolerance of the larvae. Our results also suggest a role of different SAM-methyltransferases in the adaptation, including GSMT, JHAMT, and candidates from other classes, which could be considered in future studies.